A Novel Fabrication of 3.6 nm High Graphene Nanochannels for Ultrafast Ion Transport. Issue 17 (21st February 2017) - Jung, Wonsuk; Kim, Jangheon; Kim, Soohyun; Park, Hyung Gyu; Jung, Yousung; Han, Chang‐Soo
Abstract : In an experiment based on electroosmotic ion transport, 3.6 nm high graphene nanochannels with a clean, smooth and hydrophobic surface and large slip length have 115 times greater ionic conductivity than SiO2 nanochannels.